MOTHER TONGUE AND SOCIAL ANXIETY AMONG INTERNATIONAL STUDENTS AT UPSI, MALAYSIA - Ida Fitria (State Islamic University (UIN) Ar-Raniry, 2021)
Moving abroad as international students would changes the social environment due to language, food, people and cultural diversity in a foreign country. This condition may cause the feeling of social anxiety in their new daily life. At worst, social anxiety might increase problems in cognitive, affective, and behavioral areas. This study aims to describe more about social anxiety among international students of Sultan Idris Education University according to the mother tongue, and gender as additional analysis. Research was designed by quantitative approach using descriptive, t-test and anova analyses. There were 117 International Students who completed the survey using Social Interactions Anxiety Scale (SIAS) for university students. The Anova test result reported, there is a significant difference in social anxiety among international students according to their mother tongue, p= 0.03 (p<0.05) and F = 2.326. International students who have mother tongue, English, seem had the lowest score of social anxiety (mean=2.12), followed by Indonesian (mean=2.54), followed by Korean (mean=2.57), and followed by Chinese (mean= 2.75). This study revealed international language, English, become as one factor that effected social anxiety problems among international students in the university.